Effect of slow release nitrogen fertilizers with foliar potassium and calcium application during fruit development on growth, yield, sugar content, nitrate accumulation and storage ability in melon - Ramadan, A.Y.; El-Lithy, Y.T.; Ragah, M.A. (2008)
Melon (Cucumis melo L.) Passport cultivar was cultivated in clay ioam soil during the seasons 2006 and 2007. Five slow release urea sources 46%N which were bentonite coated urea (bentonite-cu), bitumen coated urea (bitumen-cu), wax coated urea (wax-cu), rock phosphate coated urea (rock phosphate-cu) and calcite coated urea (calcite-cu) taken from Egyptian Fertilizer Development Center, beside traditionai . urea as a control, under recommended nitrogen rate (100 kg Nlfaddan), were evaluated. Foliar potassium and calcium application at concentrations (2.5 gm/liter and 5 gmlliter respectively) were sprayed at stage of fruit development. Yield, sugar content, nitrate accumulation, NPK and Ca content and storage ability in melon were caicuiated.
Includes references.
Summary in Arabic.
1
Keywords: Melons -- fertilizers; Foliar feeding; Liquid fertilizers -- Application; Nitrogen frtilizers; Melons -- storage